Look at that! : farm animals - Genechten, Guido van. (New york : Clavis Pub., 2008)
"Look at the illustrations and identify the animals. For toddlers ages 12 months and up with a focus of the child's language development".
On board pages.
Cover title.
Keywords: Domestic animals -- Juvenile fiction; Board books